2021
DOI: 10.23887/jeu.v9i2.38975
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Penggunaan Gadget terhadap Hasil Belajar dan Minat Belajar Siswa Sekolah Dasar

Abstract: Gadget merupakan alat elektronik yang digunakan sebagai media informasi, media belajar, dan sebagai hiburan. Manfaat gadget lainnya yaitu dapat tersambung dengan internet dan siswa sudah mengenal fungsi internet. Hal ini mengakibatkan banyak siswa yang menyalahgunakan penggunaan internet untuk hal negatif, sehingga siswa harus selalu dalam pengawasan orang tua. Tujuan penelitian ini adalah untuk menganalisis pengaruh penggunaan gadget terhadap minat belajar siswa kelas V sekolah dasar. Jenis penelitian yang di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
4
0
10
Order By: Relevance
“…Students will be excited to learn when they feel happy and interested and will be more motivated to continue learning (Hudaya, 2018;Kurniawati, 2020). The results obtained in this study are in line with the results of previous research, which also revealed that the use of gadgets did not significantly affect student learning outcomes and the learning interest of elementary school students (Nikmawati et al, 2021). The results of other studies show that using gadgets impacts the psychological development of elementary school children (Syifa et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Students will be excited to learn when they feel happy and interested and will be more motivated to continue learning (Hudaya, 2018;Kurniawati, 2020). The results obtained in this study are in line with the results of previous research, which also revealed that the use of gadgets did not significantly affect student learning outcomes and the learning interest of elementary school students (Nikmawati et al, 2021). The results of other studies show that using gadgets impacts the psychological development of elementary school children (Syifa et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…This research is in line with several previous studies entitled the impact of using gadgets on elementary school students' learning outcomes and learning interests. The results of this study indicate that the use of gadgets has no significant effect on student learning outcomes and significantly affects the learning interest of elementary school students (Nikmawati et al, 2021). The results of other studies show that using gadgets impacts the psychological development of elementary school children (Syifa et al, 2019).…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Namum faktanya banyak siswa sekolah dasar memanfaatkan gadget untuk mengakses media sosial dan permainan [3]. Keterlibatan siswa sekolah dasar pada gadget menyebabkan keterasingan dan kecanduan, terutama ketika siswa sekolah dasar lebih suka bermain gadget atau game daripada membaca.…”
Section: Pendahuluanunclassified
“…Penggunaan gawai tidak hanya dimanfaatkan oleh lingkungan orang tua, pekerja dan profesional lainnya, akan tetapi dizaman yang modern ini hampir semua lingkungan baik itu lingkungan dewasa ataupun anak-anak sudah menggunakan gawai dalam kehidupan sehari-sehari (Gutji, 2021). Termasuk di kalangan siswa sekolah dasar hampir setip hari mereka menggunakan gawai (Nikmawati et al, 2021). Sebagian dari orang tua siswa sudah memfasilitasi anaknya, dikarenakan agar lebih leluasa melakukan kegiatanya tanpa menemani anak bermain.…”
Section: Pendahuluanunclassified